Signal Processing in Passive Radar Systems Using 5G: A Simulation Study - Van Tuan Nguyen; V. M. Kutuzov; E. N. Vorobev (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Research into the potential use of new telecommunication signals for illumination in passive radar systems is an important task. The development of communication technologies, particularly the emergence of 5G, offers opportunities for the advancement of passive radar systems that utilize 5G transmitters as illuminators. A theoretical analysis of the 5G signal characteristics in the context of its use for illumination in passive radar systems reveals the potential for high resolution in terms of range and velocity. This article presents the results of simulations of the signal processing process in passive radar systems using a 5G signal for two scenarios: with the presence of a single object and two objects in the observation field. The limited availability of 5G networks in Russia impedes experimental studies. Therefore, simulation of the signal processing process in passive radar systems using 5G signals for object illumination is a relevant task.Aim. Analysis of 5G downlink signal and simulation of signal processing in passive radar with 5G illumination source in different scenarios.Materials and methods. The theory of signal processing in semi-active radar, 5G standard and structure, a model of the 5G signal propagation channel, and comparative analysis were used. The calculation of the cross-ambiguity function of the passive radar using the 5G signal was carried out by computer simulation.Results. The conducted simulation of the signal processing process in different scenarios found that passive radar using a 5G signal is capable of detecting targets with good resolution in terms of both range and velocity.Conclusion. The simulation results further support the potential for effective use of the 5G illumination signal in passive radar for monitoring purposes in relatively small areas.